Towards quantitative treatment of electron pair distribution function - Gorelik, Tatiana E; Neder, Reinhard; Terban, Maxwell W; Lee, Zhongbo; Mu, Xiaoke; Jung, Christoph; Jacob, Timo; Kaiser, Ute (Acta crystallographica. Section B, Structural science, 2019)
The pair distribution function (PDF) is a versatile tool to describe the structure of disordered and amorphous materials. Electron PDF (ePDF) uses the advantage of strong scattering of electrons, thus allowing small volumes to be probed and providing unique information on structure variations at the nano‐scale. The spectrum of ePDF applications is rather broad: from ceramic to metallic glasses and mineralogical to organic samples. The quantitative interpretation of ePDF relies on knowledge of how structural and instrumental effects contribute to the experimental data. Here, a broad overview is given on the development of ePDF as a structure analysis method and its applications to diverse materials. Then the physical meaning of the PDF is explained and its use is demonstrated with several examples. Special features of electron scattering regarding the PDF calculations are discussed. A quantitative approach to ePDF data treatment is demonstrated using different refinement software programs for a nanocrystalline anatase sample. Finally, a list of available software packages for ePDF calculation is provided.